2020
DOI: 10.1111/jth.15078
|View full text |Cite
|
Sign up to set email alerts
|

First‐in‐patient study of hetrombopag in patients with chronic idiopathic thrombocytopenic purpura

Abstract: Background: Idiopathic thrombocytopenic purpura (ITP) especially refractory and (or) relapsed ITP, is a serious and global health burden and its clinical treatment is far from being satisfied. Hetrombopag is a novel, small-molecule thrombopoietin receptor agonist for the treatment of chronic idiopathic thrombocytopenic purpura (CITP). Objectives: This first-in-patient study aimed to investigate the safety, pharmacokinetics, and anticipated therapeutic dose of hetrombopag in CITP patients. Methods: In this mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Only one patient's dose of hetrombopag was modified due to an AE. Liver toxicity in this study was not a new safety signal since it had been observed in a previous first-in-patient trial of hetrombopag in ITP patients (24). In the current study, most of the treatment-related increased transaminases were grades 1-2, and only 1 patient had grade 3 increased alanine aminotransferase.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Only one patient's dose of hetrombopag was modified due to an AE. Liver toxicity in this study was not a new safety signal since it had been observed in a previous first-in-patient trial of hetrombopag in ITP patients (24). In the current study, most of the treatment-related increased transaminases were grades 1-2, and only 1 patient had grade 3 increased alanine aminotransferase.…”
Section: Discussionsupporting
confidence: 51%
“…Preclinical studies have shown that hetrombopag has a similar mechanism of action as eltrombopag, but its pharmacological performance in vivo (nude mice) is superior to that of eltrombopag (23). In the first-in-patient study, hetrombopag was found to be well-tolerated and have preliminary efficacy in ITP patients (24). Thus, we conducted this phase 1 trial (NCT02614846) to further assess the activity and safety of hetrombopag in ITP patients who had an insufficient response or had progressed on a previous standard ITP treatment.…”
Section: Introductionmentioning
confidence: 99%
“…There were minimal adverse events. At the lowest dose of 2·5 mg, there was a minimal rise in platelet count and only 1/8 (12·5%) had a platelet count rise over 50 × 10 9 /l; but at doses of 5·0 and 7·5 mg there was a dose‐dependent rise in platelet count with response rates of 7/12 (58·3%) and 8/12 (66·7%), respectively, beginning on day 4–5 and reaching a peak on about day 14, then falling to baseline after discontinuation of therapy 138 …”
Section: New Tpo Receptor Agonistsmentioning
confidence: 97%
“…At the lowest dose of 2Á5 mg, there was a minimal rise in platelet count and only 1/8 (12Á5%) had a platelet count rise over 50 9 10 9 /l; but at doses of 5Á0 and 7Á5 mg there was a dosedependent rise in platelet count with response rates of 7/12 (58Á3%) and 8/12 (66Á7%), respectively, beginning on day 4-5 and reaching a peak on about day 14, then falling to baseline after discontinuation of therapy. 138 In a very large, well conducted, double-blind, placebocontrolled phase 3 study (NCT03222843), patients over 18 years with primary ITP >6 months having failed ≥1 prior treatment and with platelets <30 9 10 9 /l, received daily placebo (n = 85), hetrombopag 2Á5 mg (n = 168) or hetrombopag 5Á0 mg (n = 171) for 10 weeks. 139 Stable doses of other concurrent treatments except for other TPO-RA were allowed.…”
Section: New Tpo Receptor Agonistsmentioning
confidence: 99%
“…Because this is a new drug and there is not yet enough information, the need to find the correct doses for CITP treatment is essential. The present study by Wang et al is the first‐in‐patient report of this novel drug, which was aimed to investigate the safety, pharmacokinetics, and anticipated therapeutic dose in CITP patients 9 . The authors reported that oral hetrombopag, administered in fasting conditions, was mostly well tolerated by CITP patients, they also evaluated the anticipated therapeutic dose using three dose cohorts that consisted of 2.5, 5, and 7.5 mg/d.…”
mentioning
confidence: 99%